Auzān Jam’i at-Taksīr fī al-Lughah al-‘Arabiyyah (Dirāsah Tahlīliyyah Nahwiyyah wa Sharfiyyah fī Sūrah al-Māidah wa Tarjamatihā) - Nur Khamidah, Nur Khamidah (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2025)
In the discussion of Arabic language studies, especially in the study of Nahwu and Sharf, there is one unique discussion, namely about jama' Taksir. Jama' Taksir is divided into two (2), namely jama' Qillah and Katsrah, where these jama'-jama' have many wazans and have special characters in the formation process. The formulation of the problem in this research is (1) What are the wazan jama' Taksir in surah al-Ma'idah? (2) What is the grammatical marker for jama' Taksir in surah al-Ma'idah? (3) How is the translation of jama' Taksir in surah al-Ma'idah? This research is qualitative research using descriptive analysis and library research. The primary/main data source in this research is Surah al-Ma'idah and its translation, while the researchers took secondary/supporting data sources from journals, dictionaries or other literature, both offline and online. In collecting data, the author used the text observation/document research method. The formation of the jama' Taksir is very varied, so that discrepancies are often found in translating it. Translators often translate the jama' Taksīr in the form of reduplication (repetition), so it will result in a lot of wasted words (redundancy), even though not all reduplications mean jama'. From this research, the author found: Based on the wazan, researchers found jama' Taksir in surah al-Ma'idah as many as 123 words consisting of 53 words in the jama' Qillah category and 70 words in the jama' Katsrah category. Based on grammatical markers, researchers found 33 words in the rafa' category, 49 words in the category of nashab and 41 words in the category of jarr. Based on the translation, researchers found that 80 words were correct and 43 words were incorrect.